2012
DOI: 10.1016/j.snb.2012.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Double spiral detection channel for on-chip chemiluminescence detection

Abstract: AbstractsIn this paper reports a three layered device that consists of a double spiral channel design for chemiluminsence (CL) detection and a passive micromixer to facilitate mixing of reagents. Compared to the design with a single spiral channel, the design with two overlapping spiral channels doubled the CL intensity emitted from the reaction. Furthermore, the addition of the passive micromixer improved the signal by 1.5 times. Luminol-based chemiluminescence reaction was used for the characterization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recently, many CL probes have been developed and applied to the monitoring of various compounds . Among them, luminol, regarded as a typical strong CL reagent, has been found that its light emission can be enhanced significantly when hydroxyl compounds were added into this CL reaction. In addition, persulfate is an oxidant, which can produce weak CL emission when it is mixed with alkaline luminol. , These interesting results encourage us to explore a luminol probe-triggered CL measurement system for monitoring hydroxylated intermediates generated in AOPs.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, many CL probes have been developed and applied to the monitoring of various compounds . Among them, luminol, regarded as a typical strong CL reagent, has been found that its light emission can be enhanced significantly when hydroxyl compounds were added into this CL reaction. In addition, persulfate is an oxidant, which can produce weak CL emission when it is mixed with alkaline luminol. , These interesting results encourage us to explore a luminol probe-triggered CL measurement system for monitoring hydroxylated intermediates generated in AOPs.…”
Section: Introductionmentioning
confidence: 98%
“…Based on immunofluorescence technology, they employed the antigen–antibody reaction of lung cancer cells to realize the detection and diagnosis of early lung cancer. Lok et al [ 22 ] designed a micromixer with herringbone structures to perform luminol–hydrogen peroxide chemiluminescence detection, and the results showed that the luminescence intensity has a linear relationship with Co 2+ ion concentration or hydrogen peroxide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Most chemiluminescent biosensors rely on conventional laboratory instrumentation for the transduction of the optical signal into a digital signal. Examples include inverted optical microscope or CCD cameras [ 16 ], waveguides and in-line detection elements [ 19 ]. However, the use of transducers undermines the advantages of portability and simplicity of the microfluidic device.…”
Section: Introductionmentioning
confidence: 99%